Meridianins Rescue Cognitive Deficits, Spine Density and Neuroinflammation in the 5xFAD Model of Alzheimer’s Disease - Rodríguez-Urgellés, Ened; Sancho-Balsells, Anna; Chen, Wanqi; López-Molina, Laura; Ballasch, Ivan; Castillo, Ignacio del; Avila, Conxita; Alberch, Jordi; Giralt, Albert (Frontiers in Pharmacology, 2022)
Glycogen Synthase Kinase 3β (GSK3β) is a core protein, with a relevant role in many neuro-degenerative disorders including Alzheimer’s disease. The enzyme has been largely studied as a potential therapeutic target for several neurological diseases. Unfortunately, preclinical and clinical studies with several GSK3β inhibitors have failed due to many reasons such as excessive toxicity or lack of effects in human subjects. We previously reported that Meridianins are potent GSK3β inhibitors without altering neuronal viability. In the present work we examine whether Meridianins are capable to inhibit neural GSK3β in vivo and if such inhibition induces improve-ments in the 5xFAD mouse model of Alzheimer’s Disease. Direct administration of Meridianins in the third ventricle of 5xFAD mice induced robust improvements of recognition memory and cognitive flexibility as well as a rescue of the synaptic loss and an amelioration of neuroin-flammatory processes. In summary, our study points out Meridianins as a potential compound to treat neurodegenerative disorders associated with an hyperactivation of GSK3β such as Alz-heimer’s Disease.